Fire, climate and biotic interactions shape diversity patterns along an Afrotropical elevation gradient. (18th May 2022) - Doležal, Jiří; Dančák, Martin; Kučera, Jan; Majeský, Luboš; Altman, Jan; Řeháková, Klára; Čapková, Kateřina; Vondrák, Jan; Fibich, Pavel; Liancourt, Pierre
Abstract: Aim: Untangling multiple drivers influencing biodiversity along elevation gradients is necessary for predicting the consequences of climate change on mountain communities. We examine the direct and indirect effects of macroclimate, edaphic conditions, fire frequency and putative biotic interactions on species richness and abundance of co‐occurring primary producers on Mount Cameroon. Location: Mount Cameroon, Cameroon.Taxon: vascular plants, bryophytes and lichens, and soil microbial phototrophs. Methods: We combine ground‐level survey of multi‐taxa diversity, soil nutrient stoichiometry, continuous climate monitoring using dataloggers and remote sensing data, for 115 plots sampled along a 2200–4000 m elevation gradient. We used GAMs to assess elevational patterns in ecosystem properties and SEMs to determine their direct and indirect effects on species richness and abundance. Results: Vascular plant diversity peaked at mid‐elevation and emerged from the combined effects of intermediate levels of energy, total above‐ground standing biomass, fire frequency, guild abundances and edaphic conditions. Bryophyte–lichen diversity increased monotonically towards high elevation with decreasing temperature and increasing nutrient scarcity, while the diversity of soil phototrophs peaked at both lower elevation fire‐prone Afromontane and cold higher elevation Afroalpine zones. The role of macroclimate was indirect and scale dependent. Higher temperatures increased plant richness mainly indirectly via enhanced fire frequency, while soil N:P ratio had direct positive effect on plant richness. Precipitation decreased plant richness indirectly via decreased fire frequency. Fires also increased plant and bryophyte–lichen cover. Positive bryophyte–lichen and vascular plants associations strengthened in the Afroalpine zone. Main conclusions: We demonstrate the role of disturbance/fire and biotic interactions in mitigating macroclimate effects and in controlling variation in community diversity along elevation gradients. While the macroclimate is often a strong predictor of ecological patterns along elevation gradients, our study illustrates that attributing these patterns exclusively to climate can lead to an incorrect assessment of the impact of climate change on biodiversity.